Involvement of the 90 kDa Heat Shock Protein During Adaptation of Paracoccidioides Brasiliensis to different Environmental Conditions (2013)
ABSTRACT: HSP90 is a molecular chaperone that participates in folding, stabilization, activation, and assembly of several proteins, all of which are key regulators in cell signaling. In dimorphic pathogenic fungi such as Paracoccidioides brasiliensis, the adaptation to a higher temperature, acid pH and oxidative stress, is an essential event for fungal survival and also for the establishing of the infectious process. To further understand the role of this protein, we used antisense RNA technology to generate a P. brasiliensis isolate with reduced PbHSP90 gene expression (PbHSP90-aRNA). Reduced expression of HSP90 decreased yeast cell viability during batch culture growth and increased susceptibility to acid pH environments and imposed oxidative stress. Also, PbHSP90-aRNA yeast cells presented reduced viability upon interaction with macrophages. The findings presented here suggest a protective role for HSP90 during adaptation to hostile environments, one that promotes survival of the fungus during host–pathogen interactions.